- The Death Penalty in the Context of Human Rights (A Study of Supreme Court Decision Number 3083 K/PID.SUS/2022: Human Rights Perspective on the Death Penalty (Study of Supreme Court Decision Number 3083 K/PID.SUS/2022) - Novia Rahmawati nasution; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2024)
Every human being has Human Rights (HAM) as a creature of God whose existence and dignity must be supported and respected. When faced with human rights, the death penalty in Indonesia in narcotics crime cases always raises pros and cons. The formulation of the problem of this article is whether the imposition of the death penalty against narcotics offenders in Supreme Court Decision Number 3083 K/Pid.Sus/2022 is in accordance with human rights principles. The method used is normative juridical by analyzing laws and regulations in relation to applicable norms and data collection using the literature method. The result is that the judex facti's decision is not contrary to the law, so the defendant's cassation is rejected, because the actions of the perpetrator will greatly disturb the community and disturb the next generation if children and adolescents fall into the use of narcotics. The conclusion is shows that the death penalty for drug offenders in Supreme Court Decision Number 3083 K/Pid.Sus/2022 in Indonesia is contrary to the right to life stipulated in Article 6 of the 1966 International Covenant on Civil and Political Rights, but is in accordance with Indonesian positive law, namely Law No. 35 of 2009 concerning Narcotics.